Evaluation of Integrated Counselling and Testing Centres (ICTC) for HIV in a District of India - Mohan K. Papanna; Pawan Kumar; Avinash Shetty; Unnikrishnan Bhaskaran; Vaman Kulkarni; Sahoo Saddichha; Indira B Poojary (Universiti Kebangsaan Malaysia, 2012)
ICTCs provide a critical entry point for prevention, care and support for both people affected by HIV/AIDS and general population. The study was conducted with the objective of evaluating ICTCs in terms of infrastructure and staffing, services provided, level of utilization and quality of counselling.The structure and process evaluation of 13 ICTCs under National AIDS control programme III (NACP III) was carried out in a Coastal District of South India. The evaluation was carried out using UNAIDS Tools between July and September of 2010.Twelve out of 13 ICTCs (92%) had adequate infrastructure and staff. Most of the general clients (75%) attending ICTCs were provider initiated and 84.5% of antenatal women in the district attended pre-test counselling and also underwent HIV testing. Twenty six pre-test counselling sessions and 12 post test sero-positive counselling sessions were observed. Pre-test counselling content assessment revealed that only 57.4% of sessions address all the issues whereas, 79% of post-test sessions addressed most of the issues during counselling. Counsellors’ skills assessment information gathering and information giving were found to be poorly done. It was found that post test counselling sessions were not conducted for clients with HIV negative report.The aspects of ICTCs such as services provided at the centers, utilization of services by the clients, infrastructure and staffing pattern were found to be adequate. Counselling forms the vital component of the ICTC needed improvement and post test counselling should be mandatory to all the clients.